Pekerja Migran Indonesia di Brunei: Mengapa Bekerja di Brunei? 2021-2023 - Maliki, Musa; Prihatiningsih, Witanti; Nurul Hikmah, Reva (Mandala: Jurnal Ilmu Hubungan Internasional, 2024)
International migration is never ending issue in the era of globalization. International migration is significance discussed because it creates problems in the world. The focus of this research is to examine case study of Brunei as the destination of Indonesian migrant workers to acquire well-living and other purposes. By using phenomenological approach, this research argues that Indonesian migrant workers who seek for job opportunity in Brunei is not solely motivated by economic wellbeing, but others reasons such as escaping problems, gaining life experience, and creating distinguished image of working overseas. By applying qualitative method as such deep interview and phenomenological experience living in Brunei Darussalam for 2.5 years, as the result, this research found that the reasons Indonesian migrant workers go to Brunei Darussalam is very much complex, therefore cannot be reduced in the variable independent of economic purpose. It can be concluded that this research believes that the proses of international migration is more complex then seeking economic wellbeing. In short, Indonesian migrant workers cannot be conceptualized as the movement of international labors for achieving economic goals because Indonesian migrant workers are being a human as a whole and complex, not an atomistic entity as part of mode of production.